Multiphysics Simulation of Particle-Surface Interaction and its Effect on Powder Patterns and Process Optimization - B Siyahhan; G Boiger; A S Fallah; H Khawaja; M Moatamedi (International Journal of Multiphysics, 2023)
In industrial processes, powder coating is widely utilized to attain functional or aesthetic surface properties on manufactured parts. A Eulerian-Lagrangian Multiphysics solver has been developed within the OpenFOAM framework in order to simulate and optimize such processes with regards to coating efficiency and homogeneity. In the scope of this study, the powder particle-substrate and particle-particle interactions that occur on the surface of a substrate during the coating process are investigated. This is instigated by the observation that some particles glide over the substrate, rather than sticking to the substrate upon first contact. The phenomenon is governed by the balance of pressure, fluid shear stress traction, electrostatic particle-particle repulsion and gravity forces on the substrate. On the basis of experimental data previously gathered, it is demonstrated that the surface interactions are essential to predicting the coating outcome accurately enough, such as to serve as basis for later process-optimization steps. Furthermore, a dimensional analysis illustrates the weight of the individual force contributions on the overall force balance.